Proceedings of the 1st International Conference on Intervention and Applied Psychology (ICIAP 2017) 2018
DOI: 10.2991/iciap-17.2018.25
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived organizational support and employeers turnover intention through supportive co-worker workshop in division B at Company X

Abstract: The relationship between perceived organizational support and employee's turnover intention through supportive co-worker workshop in division B at Company X In today's business situation, retaining employee still be a major challenge to compete in the real market. The extent to which an employee is committed to the organization is often based on exchange relationship between organization and employee. Since employees are critical components in the organization, effort be must put to increase their perception o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Perceived organisational support is influenced by four factors. According to (Alfisyahri, Etikariena & Gatari, 2017), this include; fairness, organisational reward and job condition, supervisor support, and co-worker support. Fairness, equity, and justice are key to gaining employees' www.afropolitanjournals.com confidence.…”
Section: Concept Organisational Supportmentioning
confidence: 99%
“…Perceived organisational support is influenced by four factors. According to (Alfisyahri, Etikariena & Gatari, 2017), this include; fairness, organisational reward and job condition, supervisor support, and co-worker support. Fairness, equity, and justice are key to gaining employees' www.afropolitanjournals.com confidence.…”
Section: Concept Organisational Supportmentioning
confidence: 99%
“…Hal ini dikarenakan dengan adanya kebijakan perusahaan ataupun perlakukan kantor akuntan publik yang dapat meningkatkan persepsi auditor bahwa mereka dihargai dan penting bagi perusahaan maka akan membuat auditor menjadi nyaman dan ingin loyal terhadap kantor akuntan publik. Hasil ini sama dengan penelitian yang dilakukan oleh Fitria & Linda (2019), Alfisyahri (2018), Ghazali et al (2018), Treglown et al (2018, Ashraf et al (2016), Saranya & Muthumani (2015) Kalidass & Bahron (2015), Islam et al (2013), Hussain & Asif (2012) dan Tumwesigye (2010) yang menemukan bahwa persepsi dukungan organisasi memiliki hubungan yang signifikan positif terhadap retensi karyawan. Berdasarkan hasil analisis dapat disimpulkan bahwa hipotesis keenam terbukti.…”
Section: Uji Hipotesis 461 Uji Funclassified
“…POS has been noticed to be strongly associated with intention to leave a job and thus efforts to develop the exchange relationship between employer and employee may help to lessen the turnover intention (Wayne et al, 1997). Further, POS has been considered as one of the key factors that influence employees’ intention stay with it (Alfisyahri et al, 2017; Diógenes et al, 2016; Ghazali et al, 2018; Naim & Lenka, 2017; Prakosa et al, 2019). Furthermore, the study conducted by researchers (Karim et al, 2019) indicated that relationship between POS and ITS is mediated by Job Involvement.…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%